Sustainable tourism and development: the model of the Albergo Diffuso. Issue 5 (4th December 2017) - Morena, Marzia; Truppi, Tommaso; Del Gatto, Maria Luisa
Abstract : Purpose: In the light of contemporary tourist trends, this paper aims to provide insight on the topicality of the Albergo Diffuso Model, more than 30 years since this concept was developed. Design/methodology/approach: The paper is not based on any particular methodological approach, as it is a practitioner viewpoint paper. It describes both, the contemporary tourist trends and the Albergo Diffuso Model, its main characteristics and some organizational issues. Findings: The Albergo Diffuso is still a model worth implementing as it is relevant for the sustainable development of the Italian territory and of its treasures and to showcase the local traditions and the qualities of the Italian lifestyle. The Italian Government, too, has acknowledged its potential by means of some recent initiatives. Originality/value: This paper highlights the value of the Albergo Diffuso Model as a tool to match the peculiar features of the Italian territory, local development and the contemporary tourist trends.